Simultaneous Determination of Matrine and Tinidazole in Compound Lotion by RH-HPLC Method - Zhikui Yin; Suying Ma; Jincai Wang; Xiaojun Shang (Journal of Analytical Methods in Chemistry)
A simple, sensitive, and accurate RP-HPLC coupled with UV detector method was developed and validated for simultaneous determination of matrine and tinidazole in compound lotion. The chromatographic separation of the two compounds was carried out with a SinoChoom ODS-BP C18 column (5 μm, 4.6 mm × 200 mm) analytical column, using a mobile phase consisting of 0.025 mol/L potassium dihydrogen phosphate (containing triethylamine 0.05%, v/v) and acetonitrile (80 : 20, v/v) at a flow rate of 1.0 mL/min. The detection was monitored at 210 and 310 nm for matrine and tinidazole, respectively. Total run time was 12 min, and the column was maintained at 25°C. The excipients in the compound lotion did not interfere with the drug peaks. The calibration curves of matrine and tinidazole were fairly linear over the concentration ranges of 10.0–100.0 μg/mL (r=0.9954) and 20.0–200.0 μg/mL (r=0.9968), respectively. The RSD of both the intraday and interday variations was below 1.5% for matrine and tinidazole. The proposed HPLC method was validated according to International Conference on Harmonisation and proved to be suitable for the simultaneous determination of matrine and tinidazole in compound lotion.